Selective Amygdalohippocampectomy versus Anterior Temporal Lobectomy in Mesial Temporal Lobe Epilepsy: A Meta-Analysis of Seizure Control and Cognitive Outcomes - Putra, Fajar Faisal; Akhmad Imron; Muhammad Adam Pribadi (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2024)
Background: Mesial temporal lobe epilepsy (MTLE) is a common form of drug-resistant epilepsy often necessitating surgical intervention. The choice between selective amygdalohippocampectomy (SelAH) and anterior temporal lobectomy (ATL) remains a subject of debate, with each procedure offering potential advantages and disadvantages in terms of seizure control and cognitive outcomes. Methods: A comprehensive literature search was conducted across PubMed, Scopus, and Springer databases to identify studies published between 2013 and September 2024 that compared SELAH and ATL in patients with MTLE. The primary outcomes of interest were seizure freedom rates and changes in cognitive function, particularly IQ scores. A meta-analysis was performed using a random-effects model to pool the results of included studies. Results: The meta-analysis encompassed 5 studies involving 218 patients with MTLE (105 underwent SelAH, 113 underwent ATL). The pooled results demonstrated a statistically significant reduction in the odds of achieving seizure freedom following ATL compared to SelAH (odds ratio [OR] 0.38, 95% confidence interval [CI] 0.24-0.81, p = 0.008). Regarding cognitive outcomes, no significant difference was observed in Performance IQ (PIQ) between the two groups. However, a trend towards improved Verbal IQ (VIQ) was noted in the SelAH group, although this did not reach statistical significance. Conclusion: The findings suggest that SelAH may offer superior seizure control compared to ATL in patients with MTLE. While both procedures appear to have comparable effects on PIQ, SelAH may be associated with a trend towards better preservation or even improvement in VIQ. The choice between SelAH and ATL should be individualized based on patient-specific factors, including preoperative cognitive profile and the relative importance of seizure control versus cognitive preservation.